PERANCANGAN SISTEM INFORMASI PEMESANAN MAKAM BARU MENGGUNAKAN METODE RATIONAL UNIFIED PROCESS (Studi kasus pada Taman Pemakaman Umum Joglo Jakarta Barat) - Susilowati, Susi (Jurnal Pilar Nusa Mandiri, 2017)
This study aims to analyze and design a web-based information system that can help the process of ordering a new tomb in the cemetery Joglo so the process can save time and can help the officers perform data management tomb quickly and precisely. Methodology To develop the system using the RUP (Rational Unified Process) to observe the running system and conducted interviews to employees directly involved in ordering activity tomb. System design method used is the method Object Oriented Analysis and Design (OOAD) which will use the use case diagram, activity diagram, sequence diagram, and class diagram. This application is designed to use PHP software as an application program and MySQL as the database.